2013
DOI: 10.1084/jem.20131141
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Asxl1 results in myelodysplasia and severe developmental defects in vivo

Abstract: Loss of Asxl1 results in myelodysplastic syndrome, whereas concomitant deletion of Tet2 restores HSC self-renewal and triggers a more severe disease phenotype distinct from that seen in single-gene knockout mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(223 citation statements)
references
References 54 publications
8
213
1
1
Order By: Relevance
“…Ezh2 D/D mice showed a significant leukopenia, in part due to impaired lymphopoiesis as previously reported 31,32 enhanced apoptosis especially in LSK cells (Fig. 2d) 25,36 . Consistent with these findings, we found that Rx291/Ezh2 D/D LSK cells generated significantly fewer colonies in vitro than WT and Rx291 LSK cells ( (Table 1).…”
Section: Resultssupporting
confidence: 84%
“…Ezh2 D/D mice showed a significant leukopenia, in part due to impaired lymphopoiesis as previously reported 31,32 enhanced apoptosis especially in LSK cells (Fig. 2d) 25,36 . Consistent with these findings, we found that Rx291/Ezh2 D/D LSK cells generated significantly fewer colonies in vitro than WT and Rx291 LSK cells ( (Table 1).…”
Section: Resultssupporting
confidence: 84%
“…We primarily focused on 654 genes that are known to be involved in regulating hematopoietic cell development and/or to promote leukemogenesis, based on previously published studies (Abdel-Wahab et al, 2013; Chambers et al, 2007; Shlush et al, 2014). By overlapping with the DhMRs or DMRs identified above, we observed a significant number of these genes with altered 5hmC or 5mC modifications (Figures 6D and S6C–E).…”
Section: Resultsmentioning
confidence: 99%
“…49,89,90 Knockdown of Asxl1 in mouse results in impaired lymphoid and myeloid differentiation and multi-lineage cytopenias. 91 Collectively, these results suggest that both germline and somatic mutations in ASXL1 cause lower blood cell counts. The transcription factor ETS2 has been shown to regulate phenotypic switch from erythroid to megakaryocyte in acute megakaryocytic leukemia (AMKL), and overexpression of ETS2 results in altered sensitivity to chemotherapy drugs.…”
Section: Relationship Of Wbc Loci To Hematologic Disease and Therapymentioning
confidence: 92%